Europium complexes as luminescent sensitizers in persistent phosphors with potential optical energy conversion, storage, and imaging applications - Francisco, Leonardo Henrique Comini (2025)
Since their discovery, due to their unique properties of storing the excitation energy and slowly releasing it in the form of visible or near-infrared photons over a period of time which can vary from a few minutes up to several hours, persistent phosphors have found a wide range of applications in several areas such as illumination, optoelectronics, energy conversion, storage, bioimaging, anticounterfeiting, among others. Recent advances in developing long-lasting persistent phosphors often focus on tuning absorption and emission wavelength, as well as increasing persistent luminescence decay time, all of which may be achieved with the introduction of core-shell structures in these materials. The guiding principles for this approach in persistent phosphors are often based on reducing surface energy loss as well as broadening the absorption cross-section and controlling disorder in the crystal lattice to introduce suitable trap states for storing charge carriers in these materials. An interesting way to sensitize the host-activator luminescence, for example, is making use of ligand-based surface sensitization. In this context, lanthanide complexes arise as promising candidates as luminescent sensitizers due to the high molar absorption coefficient of the ligands, which may sensitize luminescence by various distinct mechanisms. Hence, in this work, europium complex-doped core-shell persistent phosphors were prepared and extensively investigated, targeting to establish a novel efficient strategy of designing core-shell persistent phosphors using highly luminescent lanthanide complexes as sensitizers.